Ocular injury awareness, knowledge, and safety practices among dental professionals, students, and supporting staff: A cross-sectional analysis - Venisha Borkar; Ajinkya M. Pawar; Krishna Prasad Shetty; Alexander Maniangat Luke; Mohammad Fareed; Mohmed Isaqali Karobari (PLoS ONE, 2026)
Background Ocular health is important in dentistry because the profession relies on visual acuity and has a high risk of splatter, aerosols, and projectiles. There is a great deal of promotion with respect to personal protective equipment (PPE), but little is known about how the awareness is turned into protective behaviour in dental practice in Indian contexts. Objective To assess the extent of knowledge, awareness, and clinical practices related to ocular safety among dental professionals, students, and auxiliary staff in India, and to identify significant discrepancies between their theoretical knowledge and practical implementation. Methodology An online cross-sectional survey was conducted among 512 dental professionals across various institutions in India by using a 27-item questionnaire that was diligently piloted and validated. The questionnaire serves to assess self-reported awareness, the incidence of ocular injuries, and patterns of eye protection for both clinicians and their patients. Results Although 86.1% of respondents reported being familiar with eye safety regulations, 62.5% reported eye injuries during clinical procedures, mainly as a result of spatter, aerosol, and removing restorations, which doesn’t suggest lack of protection but lack of protective eyewear. Responsive to the conditions mentioned, only 42.6% were compliant overall and consistent in wearing protective eyewear, while 93.6% report acknowledging the need for protective eyewear. Additionally, 13.3% had observed ocular injuries in patients, and 38.35% admitted to not providing eye protection during procedures. Conclusion There is a significant differential between the high awareness and poor uptake of ocular safety practices in Indian dentistry. This requires enhancing policy in institutions, introducing ocular protection in dental education and establishing standard procedures. Reducing preventable injuries and ensuring the safety of patients and practitioners is justified.